Relationship the Variation of Serum Vaspin and Some Biochemical Parameters Associated with Gender and BMI of Type2 Diabetic Patients - Abdalelah Saleem, Zahraa; Shaalan Sahab, Khalid (ASJ - Academic Science Journal, 2024)
Diabetes mellitus is a chronic disorder categorized by rise blood glucose with a disturbance in the use of carbohydrates, fats and proteins resulting from a deficiency in the secretion of the insulin or the action of insulin or both. The current study aimed to estimation of Vaspin and some biochemical parameters included insulin, fasting blood glucose(FBG), HbA1c, urea, creatinine, Triglyceride(TG), Total Cholesterol(TC), High-density lipoprotein (HDL), low density lipoprotein (LDL) and Very low density lipoprotein (VLDL)in blood of type2 diabetic patients, and determining the change of the ratio in patients comparing with healthy people.The serum vaspin level in patients group was significantly lower than that of the healthy subjects (p0.05).  There were a significant difference of serum FBG, HbA1c and urea levels in patients compared to controls (p0.05). The levels of TC, TG, LDL and VLDL were elevated significantly in patients when compared with controls (p